De Novo Assembly of First Mitochondrial Genome in Melicope pteleifolia (Rutaceae): Resolving Inter-Organellar Gene Transfer Events Through Integrated Chloroplast Analysis - Lijun Guo; Wenwen Shi; Yatao Luo; Kai Gao; Jingli Huang; Hong Wei; Pan Liang; Longfei He; Dong Xiao; Jie Zhan; Guangyu Zeng; Aiqin Wang (Horticulturae, 2025)
Melicope pteleifolia (Rutaceae) is a shrub or tree with high medicinal value. Although the physical features of M. pteleifolia are evident, the mitochondrial (mt) genome has yet to be investigated, and its evolutionary relationship within Rutaceae is unclear. The organelle genomes of M. pteleifolia were constructed using Nanopore and Illumina sequencing data. The circular mt genome is 780,107 base pairs (bp) long, with a GC content of 44.85%. It has 66 genes, consisting of 33 protein-coding genes (PCGs), 30 tRNA genes, and 3 rRNA genes. The length of the chloroplast (cp) genome was 158,987 bp, containing 88 PCGs, 37 tRNAs, and 8 rRNAs. The mtDNA and cpDNA contained 507 and 353 repetitive sequences, respectively. RNA editing sites were abundant in M. pteleifolia organelle genomes, including 323 sites in mtDNA and 260 sites in cpDNA. Phylogenetic research using the cp and mt genomes of M. pteleifolia and nine additional species of the Rutaceae family precisely delineates its evolutionary and taxonomic position. Ka/Ks and nucleotide diversity indicated that the majority of the PCGs in the mitochondrial genome had experienced negative selection. These findings provided comprehensive information on the M. pteleifolia mitogenome for studying phylogenetic relationships in Rutaceae, with chloroplast-derived sequences providing critical evidence for inter-organellar genome evolution.